2006
DOI: 10.1111/j.1399-3054.2006.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of castasterone level in primary roots of maize, Zea mays

Abstract: Gas chromatography-mass spectrometry analysis revealed that primary roots of maize contain 28-norcastasterone (28-norCS) and its biosynthetic precursors, cholesterol, and cholestanol, which suggests that the C 27 -brassinosteroid (C 27 -BR) biosynthetic pathway to generate 28-norCS is operative in the roots. A cell-free enzyme solution prepared from maize roots successfully mediated C24-methylation of 28-norCS to produce castasterone (CS) with the aid of S-adenosyl-L-methionine, which indicates that CS can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This agreed well with the subsequent studies of Kim et al . [ 64 , 65 ], who demonstrated that BR biosynthesis in maize indeed occurs in roots. However, another study indicated that the ZmDWF1 gene is expressed in all maize tissues (at least at the transcriptional level) with the highest degree of expression in the leaf collars and lower expression in older tissues [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This agreed well with the subsequent studies of Kim et al . [ 64 , 65 ], who demonstrated that BR biosynthesis in maize indeed occurs in roots. However, another study indicated that the ZmDWF1 gene is expressed in all maize tissues (at least at the transcriptional level) with the highest degree of expression in the leaf collars and lower expression in older tissues [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, norCS can also be methylated to yield CS, with DS acting as an intermediate. Reportedly, this conversion occurs also in monocot plants [ 47 , 65 ]. Furthermore, CS can also be produced from C 29 BRs such as homoCS or homoDS in rice [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several plants, in addition to 24-methyl BR biosynthesis, biosyntheses of C 27 -BRs (28-norBRs) from CHR to 28-norCS and C 29 -BRs (24-ethyl BRs) from STR to 28-homoCS have been demonstrated. Biochemical and molecular genetic studies of BR biosynthetic genes/proteins revealed that the same reactions in the biosyntheses of C 27 -BRs and C- 29 BRs are catalyzed by the same enzymes characterized in C 28 -BRs biosynthesis. ,,,, The crude enzyme prepared from Arabidopsis, tomato, and rice catalyzed the C-24 methylation of 28-norCS to CS and the C-28 demethylation of 28-homoCS to CS, showing that the C 27 -BR and C 29 -BR biosyntheses seem to be alternative routes for synthesizing BL and/or CS in plants. ,, We found that CHR and STR are major 4-demethylsterols in Brachypodium and that BR biosynthetic enzymes in Brachypodium have the same activities as in other plants. This suggests that the biosyntheses of C 27 -BRs and C 29 -BRs also functions in B.…”
Section: Discussionmentioning
confidence: 99%
“…5 Additionally, we have determined that the end product of C 27 -BRs biosynthesis, 28-norCS, is converted into CS, thereby indicating that two BRs biosyntheses are connected biosynthetically to maintain the steady-state level of an active C 28 -BR, CS, in the plant. 5,8 Our continuing interest in the physiological functions of multiple biosyntheses of BRs in plants prompted us to evaluate endogenous BRs in large numbers of Arabidopsis thaliana, in which a These authors contributed equally to this study.…”
mentioning
confidence: 99%